CLASSIFICATION OF FORECASTING METHODS FOR EARTH’S SURFACE DEFORMATION ABOVE THE SUBSURFACE MINING - Remez, Nataly; Vovk, Oksana; Yakovleva, Anna (Proceedings of National Aviation University (archive), 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–>Methods for determination parameters of earth’s surface deformation zones were analyzed along with classifications of their manifestations by various criteria which complete and develop existing conceptual estimation of deformation probability by the depth safety criteria.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>